Performance comparison of HTTP/2 for common e-commerce web frameworks with traditional HTTP - Md Siduzzaman, .; Hossan, Md Monir; Alom, Rakibul; Talha, Sarwar; Miah, M. Saef Ullah (IOP Publishing, 2020)
HTTP/2 is a cutting-edge Web convention predicated on Google's SPDY convention which tries to tackle the deficiencies and rigidity of HTTP/1. As e-commerce websites have become a significant medium for Online shopping, this paper demonstrates that whether HTTP/2 can authentically avail the performance of an e-commerce web browsing over HTTP or not. This paper states that we have studied about the HTTP/2 Implementation & performance analysis for prevalent web frameworks, where we have culled two different ecommerce web frameworks Laravel, WordPress (WooCommerce). At first, we have implemented two e-commerce sites in HTTP, then we have implemented those into HTTP/2. We additionally deployed them on the live server. By utilizing the Webserver Stress Tool & Selenium Web Driver, we have evaluated the performance under the sundry network environments. Selenium has given better results among all. But the webserver stress tool has exhibited some errors only for the http/2. This is our only constraint for this work. But still, we are endeavoring to resolve the problem. Simulation results have shown how HTTP/2 has influenced the page load time in our e-commerce websites. After analyzing all the simulation results, we have decided that Laravel is a more superior e-commerce web framework for both protocols, especially for HTTP/2.